2015
DOI: 10.7314/apjcp.2015.16.8.3101
|View full text |Cite
|
Sign up to set email alerts
|

Allele and Genotype Frequencies of the Polymorphic Methylenetetrahydrofolate Reductase and Lung Cancer in ther Jordanian Population: a Case Control Study

Abstract: of death after heart disease. A total of 6820 new cancer cases were registered by Jordan Cancer Registry in 2010, of these, 4921 cases (72.2%) were among Jordanians, and 1899 cases were non-Jordanians. Out of a total of 4921 new cases of cancer recorded amongst Jordanians in the 2010, of these, 2330 cases (48.1%) were males and 2519 cases (51.9%) were females (Jordan Cancer Registry, 2010). The rank order of the five most common cancers affecting Jordanians are: Breast, Colorectal, Lymphoma, Lung, and Prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…Al-Motassem et al established distribution of MTHFR c.677 C>T polymorphic variants as follows: C/C 59.6%, C/T 33.0%, and T/T 7.4%. Authors announced that patients who have C/C polymorphic variant also have an increased risk for LC [ 57 ]. Similar results on MTHFR c.677 C>T SNP distribution in LC patients were showed in our study: C/C polymorphic variant was dominating in our samples, C/C, C/T, T/T polymorphisms frequencies were respectively 58.7%, 37.0%, and 4.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Motassem et al established distribution of MTHFR c.677 C>T polymorphic variants as follows: C/C 59.6%, C/T 33.0%, and T/T 7.4%. Authors announced that patients who have C/C polymorphic variant also have an increased risk for LC [ 57 ]. Similar results on MTHFR c.677 C>T SNP distribution in LC patients were showed in our study: C/C polymorphic variant was dominating in our samples, C/C, C/T, T/T polymorphisms frequencies were respectively 58.7%, 37.0%, and 4.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that the 677 and 1298 polymorphisms could be a risk factor for different type of cancer (ARAUJO et al 2015, AL-MOTASSEM et al 2015, and could also influence the radiotherapy treatments in patients with head and neck squamous cell carcinoma, presumably through the role of MTHFR in DNA methylation (FRISO et al 2012, JONES 2015, ANDERS et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of many studies since 1995 has been the association between the 677 C>T polymorphism, plasma homocysteine concentrations, and various clinical conditions: cardiovascular diseases-CVD (FROSST et al 1995, CHRISTENSEN et al 1997, SAFFARI et al 2013, HANSON et al 2001, vein thrombosis (DJORDJEVIC et al 2011), and neural tube closure defects (VAN DER PUT et al 1998, BEAUDIN andSTOVER, 2009). More recently, the findings that individuals homozygous for 677TT exhibit lower levels of genomic DNA methylation under low folate status (FRISO et al 2012) and that global DNA hypomethylation is observed in early tumorogenesis (JONES 2005), suggested that the 677 C>T mutation could also be connected with the development of cancer (ARAUJO et al 2015, AL-MOTASSEM et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…However, the risk of population stratification in this study is unlikely because the Jordanian population is considered to be a genetically homogeneous population. Jordanians are descended from villagers and a Bedouin lineage originating in the Arabian Peninsula (27). Notably, the majority of the population is Arab (nearly 98%), and the remaining 2% is divided equally into Armenians and Circassians.…”
Section: Discussionmentioning
confidence: 99%